(3cJGH Mjd Hfi ehSis - (3HOjY GdReGf CHh GdYR CHh HcQ ESeGYjd Hf GdQRGQ GdLRQj, GHf GdQRGR GdLRQj,J (B602 (3g` s
(3ChdgG (B:s
(3bGd GdTjN GdMeO ddg GdeHOY UfYg ai GdSeGhGJ hHYO aEfi JaMUJ ef cJH GdeJYOOjf s
(3BNQgG (B:s
(3hGQJaY GdeGA ai GdEfGA hjZeQ Hjf GdedGM Edi cag hdG CcKQ ef Pdc hPdc eG CQOJ s
(3HgG CKGQ WeSs
(3HgG UhQs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B364s
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdadcs